Study Motivation, Academic Performance and Commitment Career in Accounting Profession - Sofik Handoyo (Intelektual Pustaka Media Utama, 2018)
The purpose of this study is to understand the relationship between students' motivation, academic performance, and career commitment on accounting profession among undergraduate accounting students. The background of this study is based on the phenomenon encountered by accounting undergraduate students whose academic performance is not satisfactory as well as problems related to the completion of the study and high turn-over of the accounting profession. The sample of the study involved 101 undergraduate accounting students of Universitas Padjadjaran. There are three independent variables investigated in this study namely study motivation, academic performance and commitment carrier in the accounting profession. Intrinsic interest, extrinsic interest, normative beliefs and conflict anticipation were treated as sub-variables of the study motivation. Data were obtained through an electronic questionnaire using Google Form platform. Descriptive analysis along with bivariate correlation analysis was applied in this study. The results indicate that majority of accounting undergraduate student choosing accounting study program due to intrinsic interest motivation and extrinsic interest motivation and there is no indication motivation influenced by normative beliefs motivation and conflict anticipation motivation. Intrinsic interest has a positive and significant correlation with academic performance (r=2.17, p less than 0.01) and academic performance has a positive correlation (r = 0.124) with commitment carrier in the accounting profession.